Diversity And Dominance Species Of Benthic Gastropod In Three Coastal Condition West Bali National Park - Putri Afin Nurhayati; Jordan Oktavio Marcelino; Puspanjali Prahasto; Emilia Anjar Prastiwi; Moch. Affandi; Aulia Umi Rohmatika (Biota, 2019)
The aim of this research was to determine the composition, domination, and diversity of benthic gastropod in three coastal condition of West Bali National Park, Province Bali. This research conducted with transect method. The research datas were raised at three location with different type of substrate, there are Prapat Agung Beach, Karang Sewu Beach, and Cekik Beach. The substrate type was rough sand, cobble, and smooth sand. Every location has two transect which is upright the contur and then has a few plot too with the measure of every plot is 1 m2. The interval for every transect is 100 m, while for every plot is 10 m. Ponar dredge was use to raised benthic gastropod. Identification of benthic gastropod was refer to identification key. The result of this research showed that 25 species from 14 family of gastropod founded at three coastal condition. Euplica scripta was dominated in the first location with index of domination is 57,14%, Terebralia palustris was dominated in the second location with index of domination is 93,46%, and Hastula hectica was dominated in the third location with index of domination is 100%. According to the result, we can conclude that composition, domination, and diversity of benthic gastropod are interrelated with substrate type of the coastal.